Segmental Colitis Associated Diverticulosis—A Possible Diagnosis in Teenagers - Mǎrginean, Cristina O.; Meliţ, Lorena E.; Mǎrginean, Maria O. (Frontiers in Pediatrics, 2018)
Segmental colitis associated with diverticulosis (SCAD) is manifested by active chronic inflammation of the colonic segments affected by diverticulosis, luminal-mucosal inflammation, independent of the presence of inflammation within and/or around the diverticula, and it usually spares the rectum. We present the case of a 15-year-old female admitted to our clinic due to lower digestive hemorrhage and abdominal pain in the previous week, associated with fever one day prior to admission. The patient had pallor, painful abdomen upon palpation, accelerated bowel movements, and macroscopic evidence of blood in the stools. Initial laboratory tests showed leukocytosis with neutrophilia, thrombocytosis, anemia, and elevated inflammatory biomarkers. Moreover, colonoscopy revealed multiple ulcerations, hemorrhage, and edema of the sigmoid colon; however, multiple orifices raised the suspicion of a colonic diverticulosis and this was later on confirmed through a barium enema. The histopathological examination pointed out signs of an active chronic inflammation and mucosal architectural changes associated with crypt abscesses, therefore suggesting the diagnosis of SCAD. The patient’s prognosis was favorable; her condition improved following steroid and 5-aminosalicylate therapy, without any symptoms or recurrences at the 4 months follow-up. In conclusion, SCAD is a very rare disease entity that is usually confused with other inflammatory bowel conditions. Moreover, it has not been reported in the pediatric age group until now.